O patrão, o contador e o empregado : Delmiro Gouveia nas biografias de Adolpho Santos e Lauro Góes (1940-1970) - Silva, Karla Karine de Jesus (2014)
This research reflected on the possibilities that the biography offers as a tool to product historical knowledge. To that end, two biographies are taken as object about merchant Delmiro Gouveia (1863-1917), who was from Ceará: Delmiro Gouveia (Testimony to a biographical study), by Adolpho Santos, written in 1947 and published in 1994; and Memories of a relatively well-lived past, however we wish it would never happen (1914-1917), by Lauro Alves de Campos Góes, written in 1962, never published. Gouveia was taken as a symbol of modernization in the Northeast for the regionalist discourse, icon mainly built from the memories produced about him. Owing to this, the current study investigates these two biographical productions about the industrialist, made by those ex-employees, endowed with singularities in relation to others. Aspects like language, style, structure, plot, the time that is described and the time that had been registered, the presence of cultural vestiges, politics and the economy of that time, as well as the relationship between biography and biographers are investigated. Thus, It is intended to understand whither these individual trajectories can be thought as tools to study the life of Delmiro Gouveia and his context.